The Relationship Between Parenting Style and Self-Efficacy To Premarital Sexual Behavior Of High School Students In Gunungkidul - Majid, Ilmidin (Sahabat Publikasi Kuu, 2023)
Introduction: The teenage age group is the most vulnerable category to various negative behaviors, such as risky sexual behavior. Consequently, there is an increase in adolescent health issues, such as the spread of sexually transmitted infections, unwanted pregnancies, early marriages, and abortions. Parents play a crucial role in providing the foundations of teenagers' personalities and guiding them to make responsible decisions, including those related to their sexuality. All forms of interaction between parents and teenagers manifest in the form of parenting styles. In addition to the role of parents, teenagers themselves must also have high self-efficacy to avoid premarital sexual behavior. Objective: This study aims to examining the relationship between parenting styles and self-efficacy with premarital sexual behavior among high school adolescents in Gunungkidul Regency. Method: This study is a quantitative research employing a cross-sectional study design. Results: Adolescents engaging in premarital sexual behavior have a risk of 36.21%. There is a significant relationship between parenting styles and premarital sexual behavior among high school adolescents (p < 0.05). There is also a significant relationship between self-efficacy and premarital sexual behavior. Gender and peer influence are significantly associated with premarital sexual behavior (p < 0.05), while exposure to information is not related to premarital sexual behavior (p > 0.05). The study concludes that adolescents who receive permissive parenting styles and have low self-efficacy are more likely to engage in risky premarital sexual behavior.